PROCESS MAPPING IN A DENTAL CLINIC - Nery-da-Silva, Gabriel; Kawamoto Jr., Luiz Teruo; Nery, Laiane Aparecida Soares Sena; Kawamoto, Waltraudi Orchulhak; Sanchini, Pietro Ayres (Revista Interdisciplinar de Estudos em Saúde, 2019)
This research aims to map the processes existing in a dental clinic. For such, field research procedures were adopted, which were performed at a union dental clinic located in São Paulo-SP city. The data collect was made through non-participant observation and focused (semi-structured) interview. The processes of the clinic were modeled with the aid of MS-Visio Professional 2013 software, in order to clarify the usefulness and participation of each component of the process. The flowcharts built in the research were validated with the technical coordinator of the clinic, who corrected their inconsistencies with the reality in the clinic. After that, the flowcharts were validated with an expert in management. The results make possible to understand the usefulness of each process and identify both the hierarchy of the processes and the key processes; and provide a basis for decision-making. Considering the business model of the clinic, the analysis of the results pointed out an opportunity of increasing the number of patients seen at the clinic. Process mapping provides a better understanding of the routines of the clinic as well as of their steps, and it may help managers to determine their processes and focus on them. So, it understands here that process management is applicable in dental clinics starting from process mapping. Keywords: Process management. Health management. Productivity. Dentistry. Dental practice management. MAPEAMENTO DE PROCESSOS EM UMA CLÍNICA ODONTOLÓGICA RESUMO: Esta pesquisa busca mapear os processos em uma clínica odontológica. Para tanto, adotou-se os procedimentos de pesquisa de campo, os quais foram realizados em uma clínica odontológica de sindicato localizada na cidade de São Paulo-SP. A coleta de dados foi feita por observação não participante e entrevista semiestruturada focalizada. Os processos da clínica foram modelados com o auxílio do software MS-Visio Professional 2013, de modo a esclarecer a utilidade e a participação de cada componente do processo. Os fluxogramas construídos foram validados com o coordenador técnico da clínica, que corrigiu as incoerências destes com a realidade na clínica. Após isso, os fluxogramas foram validados com um especialista em gestão. Os resultados permitem entender a utilidade de cada processo e identificar a hierarquia dos processos e os processos-chave, e fornecem uma base para tomada de decisões. A análise dos resultados apontou uma oportunidade de aumentar o número de pacientes atendidos, considerando o modelo de negócios da clínica. O mapeamento de processos permite melhor entendimento da rotina da clínica e de suas etapas e pode auxiliar os gestores a determinar seus processos e focar neles. Assim, entende-se que há aplicabilidade de gestão por processo em clínicas odontológicas a partir do mapeamento de processos. Palavras-chave: Gestão de processos. Gestão em saúde. Produtividade. Odontologia. Administração da prática odontológica.